ANALISIS ISI PESAN TWITTER @IKANATASSA DALAM MEMPROMOSIKAN NOVEL CRITICAL ELEVEN - Hikmah, Nurul; Sudrajat, Ratih Hasanah; Imran, Ayub Ilfandy (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
The development of technology, information, and communication in Indonesia are growing rapidly accompanied by the development of creative content in the Internet. The emergence of social media has become one of the newly popular media among the society which are utilized as a main weapon for business. Twitter as one of the social media and microblogging platforms is used not only as a medium of communication but also used for promotion. Ika Natassa, a well-known novel writer, uses twitter as one of media promotion in publishing her latest novel titled Critical Eleven. The purpose of this research is to understand the promotional theme of @ikanatassa?s tweets and to understand the message that dominates in @ikanatassa?s tweets in the period of May-June 2015. The method used in this research is a qualitative content analysis with inductive approach and the unit analysis were 300 tweets that related to the promotional activities of Critical Eleven. The findings showed that the content found in @ikanatassa?s tweet are divided into six categories, namely, promotion, sharing personal information, suggestions and tips, behind the scene, contests, and sneak preview. Based on the meaning linked to these six categories, the main theme of @ikanatassa?s tweets is 1,111 #CriticalEleven for Pre-order on 1st July 2015. This theme reflects the character of Critical Eleven and its relevance to the needs of the readers. While, the message that dominates in @ikanatassa?s tweets reflected promotion as the category. The dominance of this category is affected by the coming date of Critical Eleven?s pre-order, the number of interactions between Ika Natassa with her followers, and repetition of tweets about basic information of Critical Eleven?s pre-order.